Chill of the ice dragon - West, Tracey, 1965-; De Polonia, Nina (New York, NY : Branches/Scholastic Inc., 2018)
The Dragon Masters are still reeling from the desertion of Rori and her fire dragon Vulcan, when Mina, a Dragon Master from the far north, arrives with a problem--King Lars needs a fire dragon to defeat the Ice Giant who has frozen his kingdom; and so the Dragon Masters set out to find Rori and convince her to help
Mina from the Far North -- Finding Rori -- Attack Them! -- Rori's Decision -- Time for a Plan -- Before the Big Battle -- Inside the Ice Fortress -- Frost's Deep Freeze! -- Wizard vs. Giant -- Smash! -- The Power of the Giant -- Fire and Ice -- An Angry King -- You're it!
Grades 1-3
Grade 2
Keywords: Dragons -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Giants -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Wizards -- Fiction; Magic -- Fiction; Giants -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction; Action and adventure fiction